Nitrate Controls Root Development through Posttranscriptional Regulation of the NRT1.1/NPF6.3 Transporter/Sensor. Issue 2 (19th August 2016) - Bouguyon, Eléonore; Perrine-Walker, Francine; Pervent, Marjorie; Rochette, Juliette; Cuesta, Candela; Benkova, Eva; Martinière, Alexandre; Bach, Lien; Krouk, Gabriel; Gojon, Alain; Nacry, Philippe
Abstract : Although nitrate stimulates NRT1-1 transcription in all root tissues, it represses protein accumulation in lateral primordial, explaining that NRT1-1 controls lateral root development only in low nitrate medium. Abstract: Plants are able to modulate root growth and development to optimize their nitrogen nutrition. In Arabidopsis ( Arabidopsis thaliana ), the adaptive root response to nitrate (NO3   − ) depends on the NRT1.1/NPF6.3 transporter/sensor. NRT1.1 represses emergence of lateral root primordia (LRP s) at low concentration or absence of NO3   − through its auxin transport activity that lowers auxin accumulation in LR. However, these functional data strongly contrast with the known transcriptional regulation of NRT1.1, which is markedly repressed in LRP s in the absence of NO3   − . To explain this discrepancy, we investigated in detail the spatiotemporal expression pattern of the NRT1.1 protein during LRP development and combined local transcript analysis with the use of transgenic lines expressing tagged NRT1.1 proteins. Our results show that although NO3   − stimulates NRT1.1 transcription and probably mRNA stability both in primary root tissues and in LRP s, it acts differentially on protein accumulation, depending on the tissues considered with stimulation in cortex and epidermis of the primary root and a strong repression in LRP s and to a lower extent at the primary root tip. This demonstrates that NRT1.1 is strongly regulated at the posttranscriptional level by tissue-specific mechanisms. These mechanisms are crucial for controlling the large palette of adaptive responses to NO3   − mediated by NRT1.1 as they ensure that the protein is present in the proper tissue under the specific conditions where it plays a signaling role in this particular tissue.